A failure in solidarity: Ethical challenges in the development and implementation of new tuberculosis technologies - Komparic, Ana (Bioethics, 2019)
Prominent tuberculosis (TB) actors are invoking solidarity to motivate and justify collective action to address TB, including through intensified development and implementation (D&I) of technologies such as drugs and diagnostics. We characterize the ethical challenges associated with D&I of new TB technologies by drawing on stakeholder perspectives from 23 key informant interviews and we articulate the ethical implications of solidarity for TB technology D&I. The fundamental ethical issue facing TB technological D&I is a failure within and beyond the TB community to stand in solidarity with persons with TB in addressing the complex sociopolitical contexts of technological D&I. The failure in solidarity relates to two further ethical challenges raised by respondents: skewed power dynamics that hinder D&I and uncertainties around weighing risks and benefits associated with new technologies. Respondents identified advocacy and participatory research practices as necessary to address such challenges and to motivate sustained collective action to accelerate toward TB elimination. We present the first empirical examination of bioethical accounts of solidarity in public and global health. Our study suggests that solidarity allows us better to understand and address the ethical challenges that arrest the D&I of new TB technologies. Solidarity lends credence to policies and practices that address the relational nature of illness and health through collective action.